Responsible tourism in Thailand: Evidence from tour operators - Chaiyakot, Prachyakorn; Chaiyaket, Wachara; Pakongsup, Panot; Chomphusri, Thamrong (Edelweiss Applied Science and Technology, 2024)
This paper points out indicators of responsible tourism which are of strategic significance to tour operators seeking to develop their country towards achieving a competitive advantage. It looks at the extant literature covering the notions of responsible tourism and responsible tour operators. Qualitative research involved in-depth and semi-structured interview questions employed to collect responsible tourism data from tour operators’ direct experiences. The findings revealed that eighty-eight responsible tourism indicators for tour operators could be divided into five categories relating to the responsibility of tour operators, organisations’ sustainability policies, products and services, partners and clients, benefits for society and culture, economic benefits, and benefits for the environment.